The interaction of DRD2 and parenting style in predicting creativity. (March 2018) - Si, Si; Zhang, Shun; Yu, Qi; Zhang, Jinghuan
Highlights: The present study explored for the first time the interaction of DRD2 and parenting style on creativity. There was significant interaction effect of DRD2 and authoritarian parenting on creativity. The result coincides with the diathesis-stress model that people may differ in their vulnerability to environmental adversities. Abstract: The present study examined the interaction of dopamine D2 receptor gene ( DRD2 ) and parenting style on creativity. Participants were 427 Chinese undergraduate students from a project designed to identify the genetic basis of creativity. The result showed that there was significant interaction between DRD2 and authoritarian parenting when predicting creativity. Specifically, it was found that the negative effect of mother/father authoritarianism on creativity was only present when individuals were carriers of DRD2 Del (rs1799732) allele. No significant interaction of DRD2 and authoritative or permissive parenting was found. In conclusion, the present study provides the first preliminary evidence for the effect of DRD2 -parenting interaction on creativity; future studies are warranted to validate these findings.